Outcomes of dietary interventions in the prevention and progression of Parkinson's disease: A literature review - Ubaid Ansari; Alexi Omid; Dawnica Nadora; Jimmy Wen; Arman Omid; Forshing Lui (AIMS Neuroscience)
Parkinson's disease (PD) is a progressive neurodegenerative disorder characterized by motor and non-motor symptoms, primarily due to the degeneration of dopaminergic neurons in the substantia nigra pars compacta (SNpc). Factors contributing to this neuronal degeneration include mitochondrial dysfunction, oxidative stress, and neuronal excitotoxicity. Despite extensive research, the exact etiology of PD remains unclear, with both genetic and environmental factors playing significant roles. Given the increasing prevalence of PD, particularly in aging populations, effective preventive and therapeutic strategies are urgently needed. Emerging research suggests that dietary interventions might offer promising approaches to managing PD progression. This literature review examines various dietary interventions that differ in their composition and mechanisms of action, including the Mediterranean, vegan, carnivore, paleo, and ketogenic diets, and their potential neuroprotective effects. By evaluating the current evidence, this review aims to identify dietary strategies that may improve the quality of life for individuals with PD. Additionally, it explores the underlying mechanisms through which diet may influence PD pathophysiology, thus providing insights into how nutritional modifications can be integrated into holistic management plans for the disease.